Of pubs and platforms. (14th October 2019) - Miller, Daniel
Abstract: This article argues for a more explicit concern with sociality in anthropology, illustrated through a study of one of the oldest English platforms for sociality: the English pub. Using an approach derived from the study of social media, the pub is analysed in terms of the balance between structural (mainly commercial) forces and agency (mainly the desire for particular kinds of sociality). Following an introduction to the English pub, the article considers how pubs exert control over which population they serve. The next section, shows how groups of people colonize pubs, regardless of the pub's intentions. This is followed by a discussion of the various responses by pubs to this colonization. The final section, 'Scalable sociality', demonstrates how these processes combine to produce a phenomenon called scalable sociality, which is also a definition of social media: a series of platforms that can be sited along various scales and parameters of sociality. This is important because a similar tension between, on the one hand, commercial or state forces and, on the other hand, the development of new forms of sociality is increasingly common within many topics studied by anthropologists. Abstrait: Des pubs et des plateformes Résumé Cet article plaide en faveur d'un plus grand intérêt pour la socialité en anthropologie. Cette proposition est illustrée par une étude de l'une des plus anciennes plateformes anglaises en matière de socialité : le pub anglais. Via une approche dérivant de l'étude des médias sociaux, le pub est analysé en termes d'équilibre entre forces structurelles (principalement commerciales) et agencéité (principalement le désir envers certaines formes de socialité). Après une introduction au pub anglais, cet article examine comment les pubs exercent un contrôle sélectif sur leur clientèle. La section suivante décrit comment certains groupes de personnes colonisent les pubs, et ce indépendamment des intentions de l'établissement. Il s'ensuit une discussion sur les différentes réponses des pubs à cette colonisation. La dernière section montre comment ces processus se combinent pour produire un phénomène que l'auteur nomme « socialité évolutive », qui constitue également une définition des médias sociaux : une série de plates‐formes pouvant être situées à différentes échelles et selon différents paramètres de socialité. Ceci est important car on remarque de plus en plus souvent une tension similaire entre des forces commerciales ou étatiques d'une part et le développement de nouvelles formes de socialité d'autre part dans de nombreux sujets étudiés par les anthropologues.